2015
DOI: 10.4172/2161-0509.s1-005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Intakes Associated with Obesity and Overweight among Adolescents in the State of Qatar

Abstract: Background: In Arab countries particularly in Qatar, nutrition transition in food choices and dietary habits have been changed from healthy diet pattern to unhealthy fast food pattern. As a result overweight and obesity rates are increasing to alarming figures. The aim of this study is to assess the prevalence of obesity and overweight among adolescents in Qatar and its relation with their eating pattern. Methods: A cross-sectional study of 1225 adolescents (51% male and 49% female), aged 15 to 18 years, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The state of Qatar has a growing and large subpopulation (66%) of younger people (<30-year old) and according to estimates, about 57% of obese (BMI ≥ 30 kg/m 2 ) and overweight (BMI 25-30 kg/m 2 ) people are less than 30-year old [42]. Unhealthy eating habits are common among adolescents in the state of Qatar, and about three fourth of them consume sugar-sweetened drinks and skip breakfast more than three times a week [43]. Physical inactivity is an important risk factor for obesity among children, and more than half of students in the state of Qatar spend more than 2 h per day watching television, surfing internet, or playing electronic games [44].…”
Section: Discussionmentioning
confidence: 99%
“…The state of Qatar has a growing and large subpopulation (66%) of younger people (<30-year old) and according to estimates, about 57% of obese (BMI ≥ 30 kg/m 2 ) and overweight (BMI 25-30 kg/m 2 ) people are less than 30-year old [42]. Unhealthy eating habits are common among adolescents in the state of Qatar, and about three fourth of them consume sugar-sweetened drinks and skip breakfast more than three times a week [43]. Physical inactivity is an important risk factor for obesity among children, and more than half of students in the state of Qatar spend more than 2 h per day watching television, surfing internet, or playing electronic games [44].…”
Section: Discussionmentioning
confidence: 99%
“…18 However, another study was also conducted in Kuwait and was a school-based cross-sectional study. The study population was students between aged [11][12][13][14][15][16] years. The study found that 395 study participants (27.9%) had iron deficiency, using a cut-off level of (15 µg/L).…”
Section: Discussionmentioning
confidence: 99%
“…The State of Qatar, as part of the Gulf Cooperation Council (GCC), along with many Arab countries, has experienced a nutrition transition following the global trend, in which there is a substitution of healthy diet patterns, including food rich in vitamins, minerals and micronutrients such as fruits, vegetables and whole grains with unhealthy and fast food pattern including food rich in sugar, saturated fat and sodium. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 20 Additionally, good-quality diet is essential for preventing all forms of malnutrition. 9 21 22 Moreover, diet quality during childhood and adolescence is crucial in preventing and managing disease and premature death caused by non-communicable diseases. 22–24 …”
Section: Introductionmentioning
confidence: 99%